Manumycin A downregulates release of proinflammatory cytokines from TNF alpha stimulated human monocytes - Cecrdlova, Eva; Petrickova, Katerina; Kolesar, Libor; Petricek, Miroslav; Sekerkova, Alena; Svachova, Veronika; Striz, Ilja (Immunology letters, 2016)
Macrolide antibiotics such as azithromycin or clarithromycin are known to have potent anti-inflammatory and immunomodulatory effects but these properties cannot be widely used due to a risk of bacterial resistance. We studied another polyketide antibiotic, structurally related manumycin A known as a streptomycete derived farnesyltransferase inhibitor with limited antibacterial effects, with respect to its potential regulation of mRNA expression of several genes associated with proinflammatory responses. Downregulation of mRNA for IL-6, TLR-8, IL-1 beta and IL-10 was found in THP-1 cells after 4h stimulation with TNF alpha in the presence of manumycin A and downregulated TLR-8 and EGR-1 genes were observed after 8h. Among the genes upregulated in response to manumycin were HMOX-1, TNFRSF10A, IL-1R1, TICAM2, NLRP12 after 4h and only IL-1R1 after 8h. Furthermore, manumycin A was found to inhibit IL-1beta, IL-6, and IL-8 production in TNF alpha stimulated THP-1 cells and peripheral blood monocytes in a dose dependent manner (0.25-1 μM of manumycin A) without affecting cell viability. Cell viability of blood monocytes decreased by about 30% at manumycin A doses of 2-5 μM. Manumycin A also inhibited IL-18 release from THP-1 cells, while in cultures of blood monocytes, this cytokine was not detectable. That manumycin A mediated downregulation of proinflammatory genes in human monocytes confirmed by a measurement of cytokine levels in culture supernatants, together with a very limited effect on cell viability, might suggest potential anti-inflammatory properties of this polyketide antibiotic.
Keywords: messenger RNA; Cell Line; Inflammation; Anti-Bacterial Agents; antiflogistika; cytokiny; Gene Expression Regulation; Polyenes; zánět; Tumor Necrosis Factor-alpha; polyeny; Toll-Like Receptor 8; imunomodulace; Cytokines; Monocytes; Immunomodulation; TNF-alfa; regulace genové exprese; monocyty; toll-like receptor 8; Manumycin A; THP-1 cells; RNA, Messenger; polynenasycené alkamidy; Anti-Inflammatory Agents; Humans; Receptors, Interleukin-1; antibakteriální látky; protein 1 časné růstové odpovědi; Early Growth Response Protein 1; buněčné linie; receptory interleukinu-1; lidé; Polyunsaturated Alkamides